Expectations and experiences of retirement in defined contribution pensions: A study of older people in England - Rowena Crawford; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2012)
This report, funded by the National Association of Pension Funds and the Economic and Social Research Council, examines a range of quantitative evidence to shed light on how current older cohorts of defined contribution (DC) pension fund holders are approaching and dealing with retirement and annuitisation.
Keywords: 330